Culture, Identity, and Education in Rural Schools (Journal of Parents and Teachers, 2024)
The decline of mixed unitary schools in small population centers has inflicted significant demographic and social challenges on "emptied Spain." Has the centralization of education in urban areas brought any advantages? I invite a thoughtful reflection on this issue, drawing from experience, observation, and data.
Keywords: rural school; rural school clustering process; Spain's depopulation problem; technology gap; lifelong learning